RESPONSE OF SEVERAL SORGHUM VARIETIES TO POTASSIUM FOLIAR. - & Salh, Abood (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field experiment was conducted at the fields of Agriculture College , Anbar University, (alternative site Abu Ghraib) during  spring and fall seasons of 2017, to study the effect of soil and foliar application of potassium (140 kg.ha-1, 500, 1000 and 1500 mg-L-1) on growth and yield of three varieties of sorghum (Lelo, Inkath and Ishtar), The experiment was carried out according to the design of  (R.C.B.D) and in order of the split arrangement with three replicates.  Results shows, the cultivar Ishtar was superior in most studied characters such as plant height and leaf area ​​148.67, 152.25 cm, 5210, 4767 cm2.plant-1, in two seasons, respectively. The same cultivar gave the lowest number of days (from planting to 100% flowering), also it gave highest grain yield and highest harvest index which was 81.83 days and 4.93 ton.ha-1 and 25.15% respectively in spring season only. While the two varieties Lelo and Ishtar gave the lowest content of proline  leaves (2.11 and 0.18 mg.gm-1) in spring and fall seasons respectively. The highest concentration of potassium (1000mg L-1) was superior in plant height, leaf area and  grain yield (150.89, 155.78 cm, 5075, 4812 cm2 plant -1, 5.56, and 8.32 ton.ha-1) in two seasons  respectively.